Variability of carotenoids in a Musa germplasm collection and implications for provitamin A biofortification - Amah, D.; Alamu, Emmanuel Oladeji; Adesokan, Michael; Biljon, A. van; Maziya-Dixon, B.B.; Swennen, Rony L.; Labuschagne, Maryke T. (Elsevier, 2019)
Bananas are important staples in tropical and sub-tropical regions and their potential as a source of provitamin A has recently attracted attention for biofortification. A collection of 189 banana genotypes (AAB-plantains, M. acuminata cultivars and bred hybrids) was screened to determine variability in fruit pulp provitamin A carotenoid (pVAC) content using high performance liquid chromatography. Total carotenoid content in tested genotypes varied from 1.45 µg/g for hybrid 25447-S7 R2P8 to 36.21 µg/g for M. acuminata cultivar ITC.0601 Hung Tu with a mean of 8.00 µg/g fresh weight. Predominant carotenoids identified were α-carotene (38.67%), trans-β-carotene (22.08%), lutein (22.08%), 13-cis-β-carotene (14.45%) and 9-cis-β-carotene (2.92%), indicating that about 78% of the carotenoids in bananas are pVAC. High pVAC genotypes were identified for integration into biofortification strategies to combat vitamin A deficiency in developing countries.